The new era of customer experience in the omni-channel environment of a communication service provider - Rosman, Ronja (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2015)
This study discusses the evolution of an omni-channel model in managing customer experience. The purpose of this thesis is to expand the current academic literature available on omni-channel and offer suggestions for omni-channel creation. This is done by studying the features of an omni-channel approach into engaging with customers and through the sub-objectives of describing the process behind its initiation as well as the special features communication service providers need to take in consideration. Theories used as a background for this study are related to customer experience, channel management, omni-channel and finally change management. The empirical study of this thesis consists of seven expert interviews conducted in a case company. The interviews were held between March and November 2014. One of the interviewees is the manager of an omni-channel development team, whilst the rest were in charge of the management of the various customer channels of the company. The organization and analysis of the interview data was conducted topically. The use of themes related to major theories on the subject was utilized to create linkages between theory and practice. The responses were also organized in two groups based on the viewpoint to map responses related to the company perspective as well as the customers´ perspective. The findings in this study are that omni-channel is among the best tools for companies to respond to the challenge induced by changing customer needs and preferences, as well as intensifying competitive environment. The omni-channel model was found to promote excellent customer experience and thus to be a source of competition advantage and increasing financial returns by creating an omni-experience for the customer. Through omniexperience customers see all of the transactions with a company presenting one brand and providing ease and effortlessness in every encounter. The processes behind omni-channel formulation were identified as customer experience proclaimed as the most important strategic goal, mapping and establishing a unified brand experience in all (service) channels and empowering the first line personnel as the gate keepers of omniexperience. Further the tools, measurement and supporting strategies were to be in accordance with the omni-channel strategy and the customer needs to become a partner in a two way transaction with the firm. Based on these findings a model for omni-channel creation is offered. Future research is needed to firstly, further test these findings and expand the theoretical framework on omni-channel, as it is quite scarce to date and secondly, to increase the generalizability of the model suggested.